Implementasi Media Box Kartu Kata untuk Meningkatkan Kemampuan Membaca Siswa Kelas III SD Negeri 46 Ampenan Kota Mataram Tahun 2024 - Anggryani, Ayu Anggryani; Junaidi, Eka; Supriadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Reading is an activity aimed at obtaining meaning or information from a text. Therefore, reading is a fundamental skill that must be learned. However, based on the researcher’s observations at SD Negeri 46 Ampenan, several students were still found to have low reading ability. The purpose of this study was to improve students’ reading skills by using the Word Card Box learning media. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, which included planning, implementation, observation, and reflection. Data were collected through observations of learning activities, interviews with students, and reading skill tests. The results showed that the use of the Word Card Box media improved students’ reading skills in Indonesian language learning, with the average score increasing from 65 in the pre-cycle to 85 in the second cycle. These findings indicate that the Word Card Box can be used as an innovative and effective learning medium in classroom activities.